Determinants of corporate exchange rate exposure and implications for investors: Evidence from Chilean firms - Erwin Hansen; Stuart Hyde (The University of Manchester, Manchester Business School, 2010)
This paper investigates the impact of exchange rate fluctuations on the value of nonfinancial firms in Chile. Using a detailed dataset on firms' foreign activities, the potential determinants of the identified exposure are examined. Foreign exchange exposure depends on the levels of foreign currency debt and foreign currency assets. Levels of tradeables (exports and imports) do not explain exposure. Chilean firms attempt real hedges through matching foreign assets and income with foreign debt. Also firms use debt and liquidity to reduce exposure in addition to any possible derivative usage. Other firm characteristics which proxy for corporate hedging are not significant. Further, using a portfolio approach, it is demonstrated that for an investor holding exposed firms, exchange rate variations yield economically significant returns during periods of currency depreciation and appreciation.
Keywords: F31; G15; 330; foreign exchange; exposure; stock returns; international finance; hedging